Response Kailan Plants (Brassica oleraceae L.) to the Immersion Plant Growth Regulator (GA3) with Various Types Growing Media - Ginandjar, Salamet; Dikayani; Nurhakim, Fajri Syahid (Asian Journal of Agriculture and Rural Development, 2019)
Gibberellin are hormones that accelerate the germination of seeds, buds sprout, stem elongation, leaf growth, stimulate flowering, fruit development, affecting root growth and differentiation. The research aims to determine the response kailan plants (Brassica oleraceae L.) against immersion PGR gibberellin (GA3) with various types growing media have been conducted in Ciparanje Jatinangor since March 2015 to May 2015. Using a randomized block design (RAK) factorial design with three replications consisting of two factors. The first factor is the provision of PGR gibberellin (GA3) which consists of: (1) 0 ppm (2) 25 ppm (3) 50 ppm (4) 75 ppm (5) 100 ppm. The second factor is the type of growing media consisting of: (1) land (2) husk (3) cocopeat, with observation parameters plant height, leaf number, fresh plant weight, dry plant weight and dashed root. The results showed that the use of PGR gibberellin (GA3) with a concentration of (g2) 50 ppm and the type of soil planting medium (m1) of the most influential in improving growth and yield of kailan plant.